Exciplex host coupled with a micro-cavity enabling high efficiency OLEDs with narrow emission profile. Issue 14 (16th March 2022) - Wen, Ya; Wang, Ya-Kun; Zhou, Jun-Gui; Li, Jiao-Yang; He, Wei; Zhang, Yi-Jie; Zhu, Xiao-Zhao; Liao, Liang-Sheng; Fung, Man-Keung
Abstract : A combination strategy that unites an exciplex host with the micro-cavity effect is developed to resolve the color purity issue. The proposed strategy enables OLEDs to exhibit 2-fold narrower FWHM (26 nm  vs.  71 nm) and a CE of 180.2 cd A −1 . Abstract : Inter-molecular charge transfer-based donor–acceptor combination – with type-II energy transfer and known as an exciplex – has been extensively studied as a host for organic light-emitting diodes (OLEDs) due to the benefit of high efficiency. However, the broad spectral emission and full width at half maximum (FWHM) of the resulting electroluminescence lead to poor color purity, limiting their potential use in flat panel displays. We here propose a combination strategy that unites an exciplex host and a micro-cavity to resolve the color purity issue. The proposed strategy enables OLEDs to exhibit 2-fold narrower FWHM (26 nm vs. 71 nm) and a record current efficiency (CE) of 180.2 cd A −1 (CE remains 167 cd A −1 at 1000 cd m −2 ) without any external light-extraction techniques. This work offers a new strategy to achieve high efficiency and high color-purity OLEDs simultaneously.